Ein Modell zur systematischen Erfassung genuenischer Phraseme in Wörterbüchern, illustriert am Beispiel der Forschungsprojekte GEPHRAS und GEPHRAS2 - Autelli, Erica (Linguistik Online, 2022)
This paper aims at describing the innovations brought in the digital phraseography of Genoese thanks to the recent FWF projects GEPHRAS and GEPHRAS2. First, an overview on dialectal phraseography will be given, then the focus will be postponed on the Genoese one. The projects will be described, explaining the main choices that had to be made and that contribute to the innovative character of the Genoese-Italian phraseological dictionary.